DEGREE OF FARMING INNOVATIONS AND THE LEVEL OF PRODUCTIVITY OF SUGARCANE FARMERS IN THE VISAYAS, PHILIPPINES - Paulino A. Oñal, Jr.; Rena C. Juntilla; Jerryme C. Ortega (European Journal of Agricultural and Rural Education, 2021)
Farming innovations employed by sugarcane farmers is usually done by integrating the sugarcane production technologies. The main purpose is to increase productivity and sustainability of the sugarcane industry (Priyanka, et. Al. 2019) This descriptive method of research aid at determining the degree of farming innovations employed and the productivity of sugarcane farmers in the Visayas, Philippines. The 400 sugarcane farmers randomly identified at the 10 Mill Districts in the Visayas area of the Philippines. An instrument used was the agency Extension Program Guidelines that measures productivity of the farmers and degree of innovations employed by farmers, among others. The result shows that the level of productivity of sugarcane farms in the Visayas area was high and a significant difference indicates on the level of productivity of sugarcane farms when grouped as to location. The level of productivity of sugarcane farming in the Visayas in terms of indicators such as size of farm, type of soil, land topography, average rainfall received, distance of the farm to the sugar mill, farming innovations, workers’ availability and expenses per hectare was at low productivity. Significant difference in the productivity of sugarcane farming in the different Mill Districts in the Visayas area in terms of size of farm, land topography, distance of the farm to the sugar mill, farming innovations, workers’ availability, and expenses per hectare except for the type of soil and average rainfall. The degree of innovations employed by farmers does not significantly related to the productivity. Farmer’s innovations does not influence the level of productivity.